Legal Review of Default in Housing Ownership Credit (Kpr) Agreement - Kresna, Bala (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. The purpose of this study is to determine and analyze the causes of default in the Home Ownership Credit (KPR) agreement, as well as how to determine the occurrence of default in the implementation of the Home Ownership Credit (KPR) agreement. This type of research is normative legal research with a statute approach. In this study, data collection was carried out by means of document study, namely by studying, reviewing and examining legal materials related to this research. The data that has been collected both from library research and from field research are then analyzed qualitatively with descriptive methods. The results of the study indicate that the implementation of the Home Ownership Credit (KPR) agreement implemented by several banks, both government banks and private banks, is based on agreements between the bank as the creditor and the customer as the debtor which are stated in the Home Ownership Credit (KPR) agreement that has been mutually agreed upon. The factors that cause default in a Home Ownership Credit (KPR) agreement can be grouped into two groups, namely default that occurs due to the debtor's negligence in carrying out his obligations and default that occurs due to weak credit supervision by the bank which causes the debtor to deliberately default. The method of determining whether a debtor has defaulted on a Home Ownership Credit (KPR) agreement is based on an agreement between the bank and the debtor which is stated in the Home Ownership Credit (KPR) agreement. Based on the agreement, a clause is determined regarding the debtor's actions that can result in the debtor being declared in default. These actions include the debtor not paying installments according to the agreement, the debtor being in arrears on installment obligations by two installments, the debtor violating the provisions in the agreement and not carrying out his obligations as agreed in the agreement.Keywords: Agreement; Default; Mortgage.